Do We Need New Personalized Emergency Telehealth Solutions? A Survey of 100 Emergency Department Patients and a First Report of the Swiss Limmex Emergency Wristwatch: An Original Study - Malek Tabbara; Thomas Hodel; Urs Müller; Gabi Briner; Heinz Zimmermann; Aristomenis K. Exadaktylos (International Journal of Telemedicine and Applications)
Development of new personal mobile and wireless devices for healthcare has become essential due to our aging population characterized by constant rise in chronic diseases that consequently require a complex treatment and close monitoring. Personal telehealth devices allow patients to adequately receive their appropriate treatment, followup with their doctors, and report any emergency without the need of the presence of any caregivers with them thus increasing their quality of life in a cost-effective fashion. This paper includes a brief overview of personal telehealth systems, a survey of 100 consecutive ED patients aged >65 years, and introduces “Limmex” a new GSM based technology packaged in a wristwatch. Limmex can by a push of a button initiate multiple emergency call and establish mobile communication between the patient and a preselected person, institution, or a search and rescue service. To the best of our knowledge, Limmex is the first of its kind worldwide.